(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper proposes two new DC / AC multi-level hybrid bidirectional cells. PV MPPT method is used for the first cell. The second cell is called 5L – Parallel – BV (PBV) and has 5 voltage levels (5L). It is based on two parallel link groups of stacked HF cells, with two coupled inductors (CIs) and one simple cell. The use of two CIs is an interesting feature of the 5L – PBV cell. These CIs only operate on a half-cycle alternatively, with the CI inductor winding currents naturally set at 0. This paper is linked to the 3-phase 5L-PBV serial photovoltaic module. The advantage is that, with no output distortion of AC voltage due to unbalanced dc unit stress, the voltage of each DC in a multi-level inverter can be controlled. This theory allows PV system MPPT control to be easily carried out and the electricity produced overall is increased. The recent development of multiple-level inverter technology has been very important in the field of current control and high power. By using these inverters, we can adjust the induction motor’s frequency levels without changing the input power. This article presents an experimental analysis and calculation of the bearing power for the 3-phase Induction motor linked to the 5L – PBV inverter circuit in three phases. The proposed switching cell requires a new three-stage, multi-level inverter. Finally, the induction motor is connected to the 3 phase multi-phase inverter output. Through the use of the photovoltaic cell, the speed and strength of the electromagnetic torque are controlled. The layout is an input source for the PV induction engine. The results are checked using the software MATLAB Simulink